2015
DOI: 10.1016/j.solener.2015.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of solar radiation resources in Saudi Arabia

Abstract: Solar radiation resource data are the foundation of information for programs of large-scale deployment of solar energy technologies. While the solar resource in Saudi Arabia and the Arabian Peninsula was believed to be significant based on limited past data, understanding the spatial and temporal variability requires significantly more data and analysis in order to optimize planning and siting solar energy power plants. This paper summarizes the analysis of the first year of broadband solar resource measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(139 citation statements)
references
References 19 publications
3
136
0
Order By: Relevance
“…Prevention of power fluctuations is of considerable importance to solar PV. Zell et al (2015) [32] suggested that these variability statistics can be useful for understanding the impact of a variable resource on the output consistency of flat-plate PV.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of power fluctuations is of considerable importance to solar PV. Zell et al (2015) [32] suggested that these variability statistics can be useful for understanding the impact of a variable resource on the output consistency of flat-plate PV.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Is the total annual change of solar radiation occurring quickly or slowly within a certain time period? Formulas (8) and (9) were used to answer this problem. (2) Based on the previous answer, does the solar radiation at different levels vary gently or actively?…”
Section: Intensity Analysismentioning
confidence: 99%
“…The bars right of the axis refer to time intensity calculated by formula (9). The dashed line on the right side was the uniform line acquired using formula (8). If the right-hand bar surpassed the uniform line, it was concluded that the variation of solar radiation resources levels at that time interval was comparatively fast.…”
Section: Intensity Analysis Of Spatiotemporal Dynamics Of Solarmentioning
confidence: 99%
See 1 more Smart Citation
“…The solar radiation data information is of important for atmospheric research and solar energy technology deployment [4,5,6,7]. But then again, solar radiation readings vary with geographic latitude, season and time of day, due to the various positions of the sun under unpredictable weather conditions.…”
Section: Introductionmentioning
confidence: 99%